Online Prostitution in Media Social: How is the Victim Protection? - Agita Chici Rosdiana (Indonesia Media Law Review, 2022)
The focus of this study is to analyze the online prostitution that is rife in the development of crime motives today, and how it is held accountable to those involved in prostitution, including recipients of commercial sex workers. Online prostitution has mushroomed among the public and can even be accessed by ordinary people, many use this illegitimate business as a livelihood plus is an element of criminal acts, namely fraud where there are victims of commercial sex worker service users this very often happens because it is so vulnerable to committing fraud on social media plus the object of fraud related to sexual activity. The approach in this study is a comparison of law and legal interpretation within the framework of normative legal research. This study uses secondary data derived from various legal rules and related legislation. This research finds and emphasizes that the development of information and technology flows through social media presents challenges in victim protection efforts, especially in the case of online prostitution. Various studies have found that the motive for online prostitution that is rampant in Indonesia begins with fraud and fake accounts. The study also confirms that users of commercial sex worker services can be criminalized using local regulations governing prostitution, the enactment of the Lex Specialist Lex Generalis principle. Victims of fraud or commercial sex workers who are deceived by pimps or sex workers can be convicted of supporting prostitution activities in cyberspace. Victims of prostitution are not only adults but there is an element of coercion to young children to carry out prostitution, this is supported by several factors, namely environmental factors or economic factors.